Biotechnology and Agriculture in Developing Countries - Prato Barbosa, Nelson (The International Journal of Sociology of Agriculture and Food, 2021)
This multinational project intends to identify the current and potential uses of biotechnology in the agricultural and food sector of developing regions of Central Africa, India and Venezuela. Particular attention is paid to the study of biotechnological research, its applications, and social consequences in the above mentioned regions. Selected agricultural commodities will be grouped in three categories: 1) export oriented commodities; 2) commodities for domestic consumption; and 3) commodities produced for both domestic and international markets. The study will be divided in two phases. The first involves the identification of three commodities to be included in the above mentioned groups. Commodities will be selected for each of the regions studied. The second analytical phase is aimed at understanding the current and future uses of biotechnology in the production of the selected commodities. The principal objective is to understand the social consequences that the application of biotechnology generates for various social actors in the agricultures and societies of these regions of the developing World.